Numerical and experimental study of shock/turbulent flow interaction – A code validation test - Mohammad Ali, Jinnah, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia (IEM), 2012)
Link to publisher's homepage at http://www.myiem.org.my/